PENGARUH PRODUKSI KARET TERHADAP PERTUBUHAN EKONOMI DAN KESEMPATAN KERJA SEKTOR PERTANIAN DI KALIMANTAN BARAT - B01110100, ARI SUJARWO SUJARWO (Jurnal Pembangunan dan Pemerataan, 2016)
This study uses time series data ( time series ) through multiple linear regression model ( multiple regression ) using tools eviews program . Observation data is as much as 30 years in West borneo during the period 1984 to 2013Results from this study showed that the production of rubber and no significant negative effect on the pace of development in West borneo , rubber production and no significant positive effect on employment in West borneo .Keywords : rubber production , economic growth and employment